The Melancholic Animal: On Depression and Animality - Meijer, Eva (Humanimalia, 2019)
The phenomenon of depression fundamentally challenges common western ideas about what it means to be human, such as Cartesian distinctions between body and mind, and existing notions of rationality, autonomy and agency. Like madness more generally, melancholy and depression are historically shaped constructions, which interconnect at several points with constructions of animality. Focusing on these connections is helpful for rethinking depression in the human case, and for understanding nonhuman animal depression. Other animals are often neglected in studies of depression, even though they may from it too and human and animal depressions are often related, symbolically and practices. Examining the psycho-geographical dimensions of depression in connection to animality can contribute to a different discourse, aimed at interspecies healing.